2010
DOI: 10.4081/1684
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of pancreatic endocrine cells in SKH-1 hairless mice

Abstract: SUMMARYThe regional distribution and frequency of the pancreatic endocrine cells in the SKH-1 hairless mouse were studied by an immunohistochemical (peroxidase anti-peroxidase; PAP) method using four types of specific antisera against insulin, glucagon, somatostatin and human pancreatic polypeptide (PP). The pancreas of mice were divided into three portions; pancreatic islets, exocrine and pancreatic ducts. The pancreatic islets were further subdivided into three regions (central, mantle and peripheral region)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(56 reference statements)
3
7
0
Order By: Relevance
“…They have also been demonstrated to be associated with acinar cells and pancreatic duct. In the present study, similar to that found in other mouse strains [9,12,[14][15][16][17][18][19][20], we found that most of the insulin-IR cells were situated in the central regions of the pancreatic islets, and similar distributional patterns of insulin-IR cells were observed in the splenic and duodenal lobes of the ddN mouse.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…They have also been demonstrated to be associated with acinar cells and pancreatic duct. In the present study, similar to that found in other mouse strains [9,12,[14][15][16][17][18][19][20], we found that most of the insulin-IR cells were situated in the central regions of the pancreatic islets, and similar distributional patterns of insulin-IR cells were observed in the splenic and duodenal lobes of the ddN mouse.…”
Section: Discussionsupporting
confidence: 91%
“…The general distribution and frequency of somatostatin-and hPP-IR cells in the pancreas of the ddN mouse was found to be similar to that of other mouse strains [9,12,[14][15][16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations